2016
DOI: 10.1016/j.scitotenv.2015.10.111
|View full text |Cite
|
Sign up to set email alerts
|

Association between greenness, urbanicity, and birth weight

Abstract: Background More than half of the world's population lives in urban environments. Due to urban related factors (e.g. higher air pollution), urban residents may face higher risk of adverse health outcomes, while access to green space could benefit health. Purpose We explored associations between urban and green land-use and birth weight. Methods Connecticut, U.S., birth certificate data (2000-2006) were acquired (n=239,811), and land-use data were obtained from the National Land Cover Database. We focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 41 publications
5
66
1
2
Order By: Relevance
“…Results were mixed, but multiple studies found stronger associations between greenness and birth outcomes in participants or neighborhoods of lower socioeconomic status 1214,16,20. These findings suggest that the potential benefits of greenness on health may be strongest in more deprived areas.…”
Section: Resultsmentioning
confidence: 97%
“…Results were mixed, but multiple studies found stronger associations between greenness and birth outcomes in participants or neighborhoods of lower socioeconomic status 1214,16,20. These findings suggest that the potential benefits of greenness on health may be strongest in more deprived areas.…”
Section: Resultsmentioning
confidence: 97%
“…A limited number of studies have quantified exposure to green spaces (e.g., parks) using land cover datasets to assess, for instance, the proportion of parks in a participant’s administrative boundary (e.g., Census tract) or within a given radius from the subject’s address [13,15,16,1824]. Other studies have assessed the road network distance between a participant’s home address and green spaces such as parks, forests, agricultural land, and others [10,14,16,2528].…”
Section: Methodsmentioning
confidence: 99%
“…In analyses stratified by season of birth, the authors observed a negative correlation between NDVI and birth weight in births that occurred during warmer months (April-June). While other studies also found positive associations between greenness and higher birth weights overall [12,13], some studies found either positive associations that were not formally statistically significant [11], more importantly effect estimates moved towards the null with adjustment for covariates [12], and some study results were inconsistent depending on the greenness measure or outcome assessed [10,25]. The birth cohort studies encompassed diverse geographical settings, and effect sizes varied by region.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, better health outcomes are observed in neighborhood with greater area devoted to health facilities (e.g., clinics and hospitals) and institutional land (e.g., schools, square, and community centers) (Brown et al, 2009;Mobley et al, 2008). On the contrary, increased urban land use is reported to significantly associate with rising risk of adverse birth outcomes (e.g., small gestational age and low birth weight) (Ebisu et al, 2016) and asthma symptoms (Son et al, 2015). Some cases move from the urban areas to the rural places.…”
Section: Literature Reviewmentioning
confidence: 99%